1977
DOI: 10.1063/1.433707
|View full text |Cite
|
Sign up to set email alerts
|

Effusion studies of the thermal decomposition of magnesium and calcium sulfates

Abstract: The torsion-effusion method, with simultaneous torque angle and weight loss measurements, was used to study the thermal decomposition of MgSO4 and CaSO4. The initial step in the decomposition/vaporization process appears to be the evolution of an SO3 molecule from the lattice, followed by conversion to SO2 and O2 on the surface. Measurements of decomposition pressure as a function of orifice area show that both steps are kinetically hindered. The experimental results can be correlated very satisfactorily by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 12 publications
3
45
0
Order By: Relevance
“…17. The resulting values of were: −688.3 ± 7.8 kJ/mol, −567.5 ± 8.7 kJ/mol, and −403.6 ± 9.7 kJ/mol for MAPbCl 3 , MAPbBr 3 and MAPbI 3 , respectively.…”
Section: Thermal Stability: Non-ambient X-ray Diffractionmentioning
confidence: 95%
“…17. The resulting values of were: −688.3 ± 7.8 kJ/mol, −567.5 ± 8.7 kJ/mol, and −403.6 ± 9.7 kJ/mol for MAPbCl 3 , MAPbBr 3 and MAPbI 3 , respectively.…”
Section: Thermal Stability: Non-ambient X-ray Diffractionmentioning
confidence: 95%
“…Details of this method are described in Refs. [18,19]. If more than one more gas species is present in the vapor phase, then the weight-average molecular weight, M Ã , is given by the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows a Whitman-Motzfeldt (7,8) plot of the observed effusion pressure data on Ca50 4 at 1200 K for several orifice sizes (1). According to the W-M model (7,8), reciprocal observed pressure P shows a linear correlation with effective orifice area, 'ifa, where f and a are orifice force factor and area, respectively; the intercept of such a plot at zero effective orifice area is the reciprocal of equilibrium pressure, P eq .…”
Section: Cas04mentioning
confidence: 99%
“…Our goal initially was to characterize these processes thermodynamically. Since they were expected to follow the equilibrium pathway MS04(s) = MO(s) + S02(g) + h 02(g) (1) information about the reaction thermodynamics and the properties of the MSOis) phases could be obtained from measured decomposition pressures and the established properties of the products. Early on, however, effusion studies on MgS04(S) showed that only S03 was observed in the effusing gas under some conditions, rather than the dominant equilibrium products S02 and O 2 (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation